Surveillance Endoscopy After Foregut Surgery: Is It Necessary?. Issue 1 (March 2023) - Alwatari, Yahya; Scheese, Daniel; Gardner, Graham; Vudatha, Vignesh; Julliard, Walker; Puig Gilbert, Carlos; Shah, Rachit D.
Patients undergoing foregut surgeries can have de novo findings or worsening of underlying upper gastrointestinal pathologies including Barrett's esophagus and gastric intestinal metaplasia. These changes carry a potentially increased risk for malignancy development in the future raising the question of the utility of post-operative surveillance endoscopy after esophagectomy, bariatric and metabolic surgeries (Sleeve gastrectomy and Roux-en-Y Gastric Bypass), achalasia treatment, and anti-reflux surgery. In this narrative review, we conduct a literature exploration of available data on post-operative endoscopic surveillance findings following the procedures summarizing the prevalence of upper gastrointestinal pathologies and recommendations on the utility of postoperative endoscopy from established medical societies.